2018
DOI: 10.1007/s10067-018-4253-5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in patients with eosinophilic granulomatosis with polyangiitis

Abstract: Eosinophilic granulomatosis with polyangiitis (EGPA) is a rare form of vasculitis associated with asthma and eosinophilia. Endothelial dysfunction has been well documented in other types of vasculitis but not in EGPA. Thirty patients (10 men and 20 women) diagnosed with EGPA and remaining in a remission, and 58 controls (24 men and 34 women) matched for age, sex, and body mass index, were enrolled in the study. We assessed each participants for typical risk factors of cardiovascular diseases and measured serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…For example, ANCAs may trigger the release of bioactive molecules that have a role in thrombosis, inflammation, and endothelial activation [ 19 ]. This endothelial dysfunction is more prevalent in AAV patients as compared to the general population [ 20 , 21 , 22 ], is associated with the presence of inflammation proteins, particularly during vasculitis flares [ 21 , 22 ], and contributes to fibrosis, thrombosis, and atherosclerosis, beginning with preclinical target organ damage followed by overt CVD [ 23 , 24 ]. In EGPA patients, eosinophils could also have a direct role in endothelial cell injury [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ANCAs may trigger the release of bioactive molecules that have a role in thrombosis, inflammation, and endothelial activation [ 19 ]. This endothelial dysfunction is more prevalent in AAV patients as compared to the general population [ 20 , 21 , 22 ], is associated with the presence of inflammation proteins, particularly during vasculitis flares [ 21 , 22 ], and contributes to fibrosis, thrombosis, and atherosclerosis, beginning with preclinical target organ damage followed by overt CVD [ 23 , 24 ]. In EGPA patients, eosinophils could also have a direct role in endothelial cell injury [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several inflammatory diseases-including rheumatoid arthritis, inflammatory bowel disease, vasculitis, and several types of cancer-have been associated with IL-6 [26]. Furthermore, a recent study has shown that an increased serum IL-6 level occurred parallel to endothelial dysfunction in EGPA [27], suggesting it may play an important role in this disease. A previous study demonstrated that blocking the IL-6R with an antibody led to reduced Th2 cytokines and eosinophils in the lungs of OVA-sensitized mice [28].…”
Section: Discussionmentioning
confidence: 99%
“…Celemayer’s method was used to measure FMD of the brachial artery [ 22 ]. We used the technique described in detail in our previous papers [ 23 , 24 ]. The baseline sagittal diameter (D1) of a distal part of the brachial artery was measured in the M-presentation with a 10 MHz linear array ultrasonic transducer placed 2–3 cm proximal to the arterial bifurcation.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described by us, the IMT of the carotid artery was measured by ultrasound with a 10 MHz linear transducer. The thickness of the anterior and posterior walls of the common carotid arteries was measured in the longitudinal projection immediately proximal to their bifurcation [ 23 , 24 ]. We recorded the mean value of the IMT on the right and left side for analysis.…”
Section: Methodsmentioning
confidence: 99%